2020
DOI: 10.21203/rs.3.rs-26353/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The potential of CBC-derived ratios (Monocyte-to-lymphocyte, neutrophil-to-lymphocyte, and platelet-to-lymphocyte) to predict or diagnose incident TB infection in Tanzanian adolescents

Abstract: Background: Ratios of different immune cell populations (i.e., monocyte-to-lymphocyte, neutrophil-to-lymphocyte, and platelet-to-lymphocyte ratios) have been studied as a means of predicting future tuberculosis (TB) disease risk or to assist in the diagnosis of incident TB disease. No studies to-date, however, have evaluated the potential of these ratios to predict or assist in the diagnosis of incident TB infection - the first step in the natural history of TB disease. Methods: In this prospective study, we e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The NLR, which was initially used for assessing prognosis of cancer, tuberculosis infection, and autoimmune diseases, is an inflammatory factor in peripheral blood that can be used to assess prognosis of patients with CAD. [22][23][24] Previous studies have shown that the NLR is a predictor of short-and long-term poor prognosis in patients with ACS after PCI. [25][26][27][28][29][30] The MLR has rarely been reported and is considered as a novel marker of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The NLR, which was initially used for assessing prognosis of cancer, tuberculosis infection, and autoimmune diseases, is an inflammatory factor in peripheral blood that can be used to assess prognosis of patients with CAD. [22][23][24] Previous studies have shown that the NLR is a predictor of short-and long-term poor prognosis in patients with ACS after PCI. [25][26][27][28][29][30] The MLR has rarely been reported and is considered as a novel marker of inflammation.…”
Section: Discussionmentioning
confidence: 99%